Analysis and Design of Data Architecture for Logistics Company - Solanský, Viktor; Jirsák, Petr; Svitek, Dominik; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This thesis focuses on the topic of data architecture in the context of logistics. In the literature review, the main concepts of warehousing and logistics providers are introduced as well as the main areas regarding IT infrastructure such as information systems, data architecture and the relatively new concept of Big Data. In the practical part a current situation of data architecture of a concrete logistics company was monitored and analysed. Based on the findings from secondary and primary data collection regarding data architecture, adjustments regarding the current state of data architecture for logistics are proposed. Followingly, possible reporting adjustments are stated to increase visibility across the whole supply chain and increase customer satisfaction. Lastly the new Big Data architecture is proposed to increase competitiveness and support decision-making.
Vedoucí práce: Petr Jirsák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses